الإستقالل المالي للبلدية في الجزائر - لصاق سالم -تواتي احمد (جامعة المسيلة, 2024)
Since independence, Algeria has endeavoured to strengthen the municipality and to give it administrative and financial autonomy to be closer to meet local needs and expand its powers. Decentralization has passed through a number of stages, whether constitutions or laws that have been centralized in the renunciation of some of its powers in favour of the municipality. As the municipality has an independent moral and financial personality, it must secure the requirements of its citizens. This study is known as the Municipal Financial Autonomy Ratio in Algeria. municipal ", in terms of Algerian legislation and municipal people's councils from the President of the Municipal People's Assembly, The municipal's financial independence and budget to reach the results and recommendations s decision-making and financial independence from the central authority in order to fully exercise its functions and not only in a relative capacity.
Keywords: اإلستقالل المالي. ميزانية البلدية. سلطة الحلول. مصادر التمويل